Gastronomic Heritage Tourism Destination Travel Pattern Map in Kuningan Regency - Rahmi, Unique Julieta Audia; Turgarini, Dewi; Ningsih, Caria (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2023)
Kuningan district in West Java Province has a local food has uniqueness as gastronomic cultural heritage destination. Integrative information about gastronomic heritage tourism destinatio was not yet available, so tourist cannot easy to choose to visit industry who sell local food as tourist attraction. The general objective is to identify and map the locations of the potential Kuningan local food which can later be used by various stakeholders such as local governments, local culinary business actors, the travel industry, including tourists. While the specific objectives of this study are: (1) identifying potential of Kuningan local food, (2) making a map of the location of potential local food sales in Kuningan District. This study uses a descriptive-qualitative research method in the identification of typical/unique culinary tourism in Kuningan. Data collection techniques were carried out through participatory observation, interviews and literature studies. Data collection through observation and interviews was conducted in local government agencies, the travel industry and culinary tourism businesses in Kuningan District. Literature studies cover all concepts and theories related to culinary tourism, especially culinary references in Kuningan. The results obtained from this study indicate that there are quite a lot of potential local food of Kuningan with their own unique identity. Another result is a map of the location of the potential Kuningan local food sales that can be used by stakeholders in developing Kuningan culinary tourism.